Tracking progress: an update on animal models for Duchenne muscular dystrophy - Dominic J. Wells (The Company of Biologists, 2018)
Duchenne muscular dystrophy (DMD) is a progressive, fatal, X-linked monogenic muscle disorder caused by mutations in the DMD gene. In order to test treatments for DMD, a range of natural and engineered animal models have been developed, including mice, rats, dogs and pigs. Sui and colleagues have now added a dystrophic rabbit model to this range using CRISPR/Cas9 to disrupt exon 51 of DMD. Rabbits have the advantage of being easier to breed and less costly than dog or pig models, but having clear clinical signs, in contrast to many mouse models. There appears to be an effect of body size in models of DMD, as the severity of the clinical signs increases with increasing body size across species. All DMD models have advantages and disadvantages, and it is crucial that investigators understand the limitations of each model when testing novel therapies for DMD in pre-clinical studies.